The Physiological Impacts of the Low- and Moderate-Volume-HIIT with or without Nano-Curcumin Supplement in Women in Menopause with Obesity - Valiollah Dabidi Roshan; Sepideh Noorbakhsh; Seyedeh Fatemeh Ziatabar Ahmadi; Mehdi Nikseresht (Advances in Public Health)
Tabata exercise has been proposed as an extremely time-efficient high-intensity interval training (HIIT) method to achieve health benefits, but direct comparisons between the low-volume-HIIT (LV-HIIT), moderate-volume-HIIT (MV-HIIT) with and without nano-curcumin (NaC) supplement for 8-week on cardiovascular hemodynamic, respiratory function, muscular fitness, and physical performance in the obese menopause women are limited. In a double blind, randomized, placebo-controlled study, 53, moderately obese menopause women (average age 45–60 yrs, BMI > 30 kg/m2, WC for >85 cm, and body fat > 35%) were randomly assigned to undertake either LV-HIIT, MV-HIIT, or NaC supplement (daily 80 mg in two 40-mg capsules) for two sessions per week for 8 weeks. The maximal exercise testing after 8-week of the LV-HIIT and MV-HIIT interventions caused significantly increase in the VO2max (mean difference: 6.83 (95% CI: 25.58–43.51), p=0.01, mean difference: 5.31 (95% CI: 23.98–39.02), p=0.028), and oxygen pulse (mean difference: 0.02 (95% CI: 0.16–0.19), p=0.04, mean difference: 0.04 (95% CI: 0.17–0.21), p=0.02), respectively. Moreover, MV-HIIT with and without NaC had significant improve in muscular fitness and physical performance (hand grip in MV + NaC (mean difference: 3.8 (95% CI: 21.46–31.81), p=0.02), quadriceps strength in MV (mean difference: 14.58 (95% CI: 52.75–69.82), p=0.01), MQI (mean difference: 31.23 (95% CI: 112.67–197.15), p=0.02, mean difference: 31.52 (95% CI: 159.13–184.07), p=0.01), sit to stand test (mean difference: 1.84 (95% CI: 6.60–8.41), p=0.02, mean difference: 1.78 (95% CI: 6.69–9.03), p=0.01), and the running distance (mean difference: 96.95 (95% CI: 470.05–637.42), p=0.02, mean difference: 114.53 (95% CI: 458–641.87), p=0.02)), when compared to baseline. In compared with the LV-HIIT groups, the MV-HIIT could improve FVC (mean difference: 0.12 (95% CI: 2.21–3.26)). Our data demonstrated that both the LV-HIIT and MV-HIIT, as part of activities of daily living, maybe a time-efficient strategy to improve cardiorespiratory fitness and physical performance. Beyond the purported health benefits, the MV-HIIT with and without NaC supplement appears to be safe approach in the previously sedentary obese menopause women.